Knowledge and Pattern of Mental Health Care Practices in Buea Health District - Ghangha, Ghangha Jamin; Fobellah, Nkengafac N.; Ateghang-Awankem, Bernadette; Atanga, Ndeso Sylvester (Advances in Social Sciences Research Journal, 2021)
Background: According to the WHO, mental health is “a state of well-being in which the individual realizes his or her own abilities, can cope with the normal stresses of life, can work productively and fruitfully, and is able to make a contribution to his or her community”. Healthcare providers especially in primary health care play a major role in the management of individuals who are mentally challenged. This study describes the knowledge and mental health care delivery patterns in the Buea Health District. Methods: We conducted a hospital- based cross-sectional study in 15 randomly selected health care facilities in the Buea Health district. Structured questionnaires were administered to healthcare providers (doctors, nurses and counselors/psychologists) in the selected health facilities to assess their level of knowledge and type of mental health care rendered to clients in Buea community of the south west region of Cameroon. Results: Out of a total of 300 questionnaires distributed, 292 were returned giving a response rate of 99.3%. Of the 292 participants, 117 (40.1%) health care providers had low knowledge levels of mental health disorders. Similarly, 114 (39.0%) of HCP (Health Care Providers) did not practice mental health care delivery in conformity to acceptable standards. HCP who had attained the Masters level of education and who had 7-10 years of work experience were more likely to have good knowledge on mental health disorders (OR = 1.33, CI = 0.10-6.56, P-value = 0.030 and OR = 0.51, CI = 0.19-0.59, P-value = 0.001 respectively), compared to less trained professionals. Regarding practice, being a female was a most likely factor for good practice of mental health care (OR = 0.82, CI = 0.49 – 0.38, P-value = 0.024) compared to being a male. Conclusion: Knowledge levels among practitioners of mental disorders and practiced care in the Buea Health District is below acceptable standards. There is an urgent need to train HCPs in mental health and ideal practice situations for the improvement of mental health care delivery in the district and the region.